Evaluation for Released and Promising Genotypes of Potato against Red Ant - Sharma, Prem Nidhi; Adhikari, Ram Chandra; Khatri, Bhim Bahadur; Upadhyay, Kalika Prasad (Journal of Nepal Agricultural Research Council, 2019)
Red ant is the most destructive insect pest of potato tubers in the field. Utilization of varietal resistance is the best option to control the pest. The resistance of five released and nine promising genotypes of potato were evaluated against red ant (Dorylus orientalis Westwood) under natural infestation in red ant prone field. Potato resistance was evaluated based on tuber damage index value (0.00 to 1) which was calculated on the bases of the percentage of damaged tubers and number of injuries on per kilogram of tubers made by the pest. Based on the results of combined data, the levels of varietal damage were categorized to be less damaged (TDI value ranging from 0.35 to 0.49), moderately damaged (TDI value ranging from 0.50to 0.64) and highly damaged (TDI value ranging from 0.65 to 0.79) types. Among the 14 genotypes compared for levels of tuber damage, the fivegenotypes: IPY-8 (TDI value: 0.35), Khumal Seto (TDI value: 0.39), PRP-056267.1 (TDI value: 0.40), Janak Dev (TDI value: 0.44) and PRP-25861.1 (TDI value: 0.49) were determined to be the less damaged types. The less damaged potato genotypes can be used by farmers as the relatively resistant genotypes against red ant.